2020
DOI: 10.3389/fcell.2020.586757
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Regulation of Cancer Development by Neuro-Endocrine-Immune Signaling Network at Multiple Levels

Abstract: The overarching view of current tumor therapies simplifies cancer to a cell-biology problem in which neoplasms are caused solely by malignant cells and the exploration of carcinogenesis and tumor progression largely focuses on somatic mutations and other genetic abnormalities of cancer cells. The limited therapeutic response indicates that cancer is driven not only by endogenous oncogenic factors and reciprocal interactions within the tumor microenvironment, but also by complex systemic processes. Homeostasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Pulmonary neuroepithelial bodies (NEB) are innervated serotonin (5-HT)-producing cells distributed throughout the airway epithelium. Studies have reported that 5-HT secretion can stimulate cancer progression, including cancer proliferation, migration, and invasion [ 20 , 21 ]. The data in Figure 1 provide evidence that AZ, SFN, and their combination show dose-dependent reduction in scratch wound closure by the bronchial carcinoid H727 (typical carcinoid) cells.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary neuroepithelial bodies (NEB) are innervated serotonin (5-HT)-producing cells distributed throughout the airway epithelium. Studies have reported that 5-HT secretion can stimulate cancer progression, including cancer proliferation, migration, and invasion [ 20 , 21 ]. The data in Figure 1 provide evidence that AZ, SFN, and their combination show dose-dependent reduction in scratch wound closure by the bronchial carcinoid H727 (typical carcinoid) cells.…”
Section: Resultsmentioning
confidence: 99%
“…The explored connection between the nervous system and tumor tissue is not surprising, as they share a reciprocal impact. On the one hand, nerve fibers or neurotransmitters in tumor tissues not only can act on fibroblasts in the microenvironment by modulating the extracellular matrix synthesis or shaping synaptic-like connections with tumor cells ( 30 ) but also has a direct effect on immune cells, thereby regulating the infiltration of immune cells into tumors ( 7 , 8 ). On the other hand, the invasion of the surrounding nerves by cancer cells also provides a route for metastasis and promotes tumorigenesis via the crosstalk between neuron cells and tumor cells ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…As important messengers of neural signaling, neurotransmitters and their receptors contribute to tumor proliferation, angiogenesis and tumor metastasis (3)(4)(5)(6). Additionally, neurotransmitter receptors are widely expressed on the surface of immune cells and regulated by their corresponding neurotransmitters, thus affecting tumor immune responses (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of neuroendocrine factors in various cancers has been emphasized in recent research [ 30 , 37 , 38 ]. Studies on somatostatin, ever since its discovery, have demonstrated its inhibitory effects on the secretion of numerous hormones, as mentioned above.…”
Section: Somatostatin and Hepatocellular Carcinomamentioning
confidence: 99%